2017
DOI: 10.1016/j.bbamcr.2017.01.009
|View full text |Cite
|
Sign up to set email alerts
|

The UPR reduces glucose metabolism via IRE1 signaling

Abstract: Neurons are highly dependent on glucose. A disturbance in glucose homeostasis therefore poses a severe risk that is counteracted by activation of stress responses to limit damage and restore the energy balance. A major stress response that is activated under conditions of glucose deprivation is the unfolded protein response (UPR) that is aimed to restore proteostasis in the endoplasmic reticulum. The key signaling of the UPR involves the transient activation of a transcriptional program and an overall reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 45 publications
0
24
1
Order By: Relevance
“…A shift in energy balance by dietary alterations and increased oxidative stress levels may play an important role in the mechanisms governing protein homeostasis like the UPR (van der Harg et al, 2017, Yilmaz, 2017. In contrast to our findings, several studies have demonstrated increased ER stress and a consequent activation of the UPR in chronic metabolic diseases such as obesity (Hotamisligil, 2010, Ozcan, Cao et al, 2004.…”
Section: Discussioncontrasting
confidence: 86%
“…A shift in energy balance by dietary alterations and increased oxidative stress levels may play an important role in the mechanisms governing protein homeostasis like the UPR (van der Harg et al, 2017, Yilmaz, 2017. In contrast to our findings, several studies have demonstrated increased ER stress and a consequent activation of the UPR in chronic metabolic diseases such as obesity (Hotamisligil, 2010, Ozcan, Cao et al, 2004.…”
Section: Discussioncontrasting
confidence: 86%
“…This finding is in line with a recent report demonstrating that silencing XBP1 in glioma cells inhibits glycolysis resulting in reduced ATP production and decreased cancer cell survival [ 26 ]. Long-term activation of the IRE1 signaling has also been shown to reduce glucose metabolism and mitochondrial function; however, it is unclear whether this effect is mediated by XBP1 [ 27 ]. Intriguingly, deficiency of XBP1 has been shown to induce an overactivation of IRE1, contributing to enhanced inflammation and apoptosis [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ER is a site of significant metabolic regulation. The UPR plays a major role in the regulation of glycolysis and it was recently shown that IRE1 mediates a metabolic decrease upon glucose shortage in neurons, suggesting an important role for the UPR as an adaptive response mechanism in relation to energy metabolism [291]. Moreover, mTOR signalling adjusts global protein synthesis, which is a highly energy consuming process, and thereby regulates energy metabolism (reviewed in [292]).…”
Section: Metabolismmentioning
confidence: 99%